Afterslip and viscoelastic relaxation model inferred from the large-scale post-seismic deformation following the 2010 Mw 8.8 Maule earthquake (Chile). Issue 3 (7th March 2016) - Klein, E.; Fleitout, L.; Vigny, C.; Garaud, J.D.
Abstract: Megathrust earthquakes of magnitude close to 9 are followed by large-scale (thousands of km) and long-lasting (decades), significant crustal and mantle deformation. This deformation can be observed at the surface and quantified with GPS measurements. Here we report on deformation observed during the 5 yr time span after the 2010 M w 8.8 Maule Megathrust Earthquake (2010 February 27) over the whole South American continent. With the first 2 yr of those data, we use finite element modelling (FEM) to relate this deformation to slip on the plate interface and relaxation in the mantle, using a realistic layered Earth model and Burgers rheologies. Slip alone on the interface, even up to large depths, is unable to provide a satisfactory fit simultaneously to horizontal and vertical displacements. The horizontal deformation pattern requires relaxation both in the asthenosphere and in a low-viscosity channel along the deepest part of the plate interface and no additional low-viscosity wedge is required by the data. The vertical velocity pattern (intense and quick uplift over the Cordillera) is well fitted only when the channel extends deeper than 100 km. Additionally, viscoelastic relaxation alone cannot explain the characteristics and amplitude of displacements over the first 200 km from the trench and aseismic slip on the fault plane is needed. This aseismic slip on the interface generates stresses, which induce additional relaxation in the mantle. In the final model, all three components (relaxation due to the coseismic slip, aseismic slip on the fault plane and relaxation due to aseismic slip) are taken into account. Our best-fit model uses slip at shallow depths on the subduction interface decreasing as function of time and includes (i) an asthenosphere extending down to 200 km, with a steady-state Maxwell viscosity of 4.75 × 10 18 Pa s; and (ii) a low-viscosity channel along the plate interface extending from depths of 55–135 km with viscosities below 10 18 Pa s.